2019
DOI: 10.19080/artoaj.2019.19.556098
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Fertilizer Application to Increase Growth and Yield of Sweet Pepper under Potassium Levels

Abstract: Potassium foliar feeding is great significance for plants because its includes low cost, quick response to plant, small quantity of potassium and it provides compensation for lack of soil fixation determine [3]. This experiment aimed to study the effect of potassium fertilizer and lithovit nano particles as foliar spray alone and combined with potassium, to see its effect on pepper plants growth as well as its water relation and some chemical components and yield production and its components. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
3
0
0
Order By: Relevance
“…All these factors resulted in the improvement of the fruit quality and the total yield. The same results were consistent with Colla et al 2010and Kroggel and Kubota, 2017and Abd El-All (2019.…”
Section: Discussionsupporting
confidence: 90%
“…All these factors resulted in the improvement of the fruit quality and the total yield. The same results were consistent with Colla et al 2010and Kroggel and Kubota, 2017and Abd El-All (2019.…”
Section: Discussionsupporting
confidence: 90%
“…As for the effect of both potassium phosphate and zinc oxide nano composites foliar application and their influence on chemical constituents of potato tubers, results obtained and presented in Table (6) show that 8 ml / l of nano potassium phosphate and 9 ml / l of nano zinc oxide gave the highest percentage of dry matter, specific gravity, total carbohydrates and starch percentage in potato tubers during the two successive seasons. This finding agree with that obtained by Abd El-All [53] who found that the highest concentration of nano phosphorus and potassium led to the highest content of pepper fruits carbohydrates content; Mijwel and Muhsin [65] who declared that the highest levels of nano phosphorus, potassium and zinc scored the highest percentage of starch in potato tubers, also Amin and Badwy [66] who stated that high levels of nano zinc resulted high carbohydrates content in common bean seeds. Similarly, Al-Juthery et al [63] found that spraying potato plants with nano phosphorus, potassium and zinc with high levels led to an increase in tubers dry matter.…”
Section: Chemical Constituents Of Tuberssupporting
confidence: 91%
“…Regarding the effect of the interaction between both foliar application treatments, it was observed that 8 ml / l of potassium phosphate and 6 ml / l as well as 9 ml / l of zinc nano composites gave higher values for all previous characters than other treatments. Concerning nano potassium phosphate composite similar result was obtained by Abd El-All[53] who stated that the highest concentration of nano phosphorus and potassium scored the highest plant height and shoot dry weight of pepper and Mahdieh et al[54] who reported that nano zinc has an effective role on enhancing vegetative growth characters of pinto bean plants. The simulative effect of nano phosphorus might be related to the role of phosphorus in the installation of energy compounds such as ATP and ADP which reflect on enhancing growth…”
supporting
confidence: 76%